Representasi Keimanan pada Karakter Kiran dalam Film Tuhan Izinkan Aku Berdosa (Analisis Semiotika Roland Barthes) - Ambarwati, Rani Tri; Suparto, Diryo; Florina, Ike Desi (CV. ITTC INDONESIA, 2025)
The movie “Tuhan Izinkan Aku Berdosa” illustrates problems related to the phenomenon of religion that is only a formality, without deep spiritual meaning. In addition, there are conflicts and oppression against women that are politicized under the pretext of religion, as well as a crisis of faith experienced by individuals due to traumatic experiences and social injustice. The inner conflict of Kiran's character becomes a real reflection of the struggle between faith and a social reality full of oppression and discrimination. This research aims to analyze the representation of Kiran's faith, as well as reveal how the film criticizes traditional religious norms and the oppression of women in the context of modern Indonesian socio-culture that is still patriarchal. This research uses a qualitative approach with Roland Barthes semiotic analysis. The analysis technique includes the identification of denotative, connotative and mythical signs in the narrative and visual symbols of the film to reveal hidden meanings about faith and social criticism and power dynamics in the context of religion.The final findings of the study show that the film “God Permits Me to Sin” represents faith in various ways, including the use of the concept of the Five Pillars of Faith which is full of inner struggles and religious practices that are not always normative. The representation of faith in Kiran's character does not only depict formal religious observance, but rather explores Kiran's life journey as a reflection of a dynamic faith and religious practice.